Molecular Mechanism of Macrophage Activation by Red Ginseng Acidic Polysaccharide from Korean Red Ginseng - Se Eun Byeon; Jaehwi Lee; Ji Hye Kim; Woo Seok Yang; Yi-Seong Kwak; Sun Young Kim; Eui Su Choung; Man Hee Rhee; Jae Youl Cho (Mediators of Inflammation)
Red ginseng acidic polysaccharide (RGAP), isolated from Korean red ginseng, displays immunostimulatory and antitumor activities. Even though numerous studies have been reported, the mechanism as to how RGAP is able to stimulate the immune response is not clear. In this study, we aimed to explore the mechanism of molecular activation of RGAP in macrophages. RGAP treatment strongly induced NO production in RAW264.7 cells without altering morphological changes, although the activity was not strong compared to LPS-induced dendritic-like morphology in RAW264.7 cells. RGAP-induced NO production was accompanied with enhanced mRNA levels of iNOS and increases in nuclear transcription factors such as NF-κB, AP-1, STAT-1, ATF-2, and CREB. According to pharmacological evaluation with specific enzyme inhibitors, Western blot analysis of intracellular signaling proteins and inhibitory pattern using blocking antibodies, ERK, and JNK were found to be the most important signaling enzymes compared to LPS signaling cascade. Further, TLR2 seems to be a target surface receptor of RGAP. Lastly, macrophages isolated from RGS2 knockout mice or wortmannin exposure strongly upregulated RGAP-treated NO production. Therefore, our results suggest that RGAP can activate macrophage function through activation of transcription factors such as NF-κB and AP-1 and their upstream signaling enzymes such as ERK and JNK.